The Role of Mobile Courts in the Enforcement of Laws in Bangladesh - Hosen, Gazi Delwar; Ferdous, Syed Robayet (Northern University Journal of Law, 2014)
Mobile court ventilates a praiseworthy neo-paradigm in the whole gamut of enforcing laws in the adversarial legal tradition of common law system in Bangladesh. The very outline of mobile courts, in terms of its structure, legal basis, modus operandi, functioning, efficacy, judicial activism, etc. are concerned, it is axiomatically proved that the mobile court is an admixture of inquisitorial and adversarial legal traditions of civil and common law legal system as a hybrid legal system for ensuring justice through dynamic implementation of law. Mobile court is probably the most popular and effective government institution to materialize the laws which is a core demand of millions of down trodden people in Bangladesh, thereby providing an avenue of hope for this nation. At the infancy stage of mobile court, we discover multi- dimensional problems in terms of its functioning, legal basis, logistic support, acceptance to the vested segment and people at large. But notwithstanding these multi-faceted acid tests, mobile court takes place an unparallel and distinctive place to protect and preserve consumer protection, sound public heath, law & order situation and ultimately justice through the proper enforcing of existing concomitant laws. This is high time for all of us to launch profound research and investigations to find out its lacunae so as to establish a full-fledged and robust socio-legal background for mobile court so that it can work with its full bloom. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18527 Northern University Journal of Law Vol.1 2010: 82-95